Prevalência, sazonalidade e intensidade de infecção por Diplostomum (Austrodiplostomum) compactum Lutz, 1928 (Digenea, Diplostomidae), em peixes do reservatório de Volta Grande, Estado de Minas Gerais, Brasil - Martins, Maurício Laterça [UNESP]; Paiva, Andresa de Mello e Faro Conceição [UNESP]; Fujimoto, Rodrigo Yudi [UNESP]; Canello Schalch, Sérgio Henrique [UNESP]; Colombano, Neidson Carneiro [UNESP] (My University, 2002)
The present study was conducted in the Aquaculture Station of Hydroeletric Power Station situated in Volta Grande Reservoir, MG, Brazil. Seventy freshwater corvinas, Plagiscion squamosissimus, and 66 tucunarés, Cichla ocellaris were captured bimonthly from April 2000 through April 2001 with net and hook. The helmints were identified as Diplostomun (A.) compactmn which showed the highest prevalence in the corvina's eyes in April 2000 (70%), February 2001 (80%) and April 2001 (60%), while in tucunaré occurred in April 2000 (33.3%), August 2000 (18.2%) and October 2000 (18.2%). Nevertheless, increase in the mean intensity of parasites was related in April (6.6), June (6.0), August (18.5) 2000 and February (5.7), April (4.8) 2001 for corvina and in August (16.0) and October (7.0) 2000 for tucunaré. Corvina's females showed infection during all period, while males did not show the same prevalence in June 2000 and April 2001. On the other hand, tucunare's males were infected in all months while females in August and October 2000. The highest prevalence in corvina was observed in the months which presented elevated water temperature (April, October, December 2000 and April 2001). The number of parasites collected in corvina on February 2000 was higher than the one observed in August 2000. The same was not observed for tucunaré. This work demonstrate corvina's high susceptibility to metacercariae of Diplostomum.
Prevalence, seasonality and infection intensity by Diplostomum (Austrodiplostomum) compactum Lutz, 1928 (Digenea, Diplostomidae) in fish of the Volta Grande Reservoir, state of Minas Gerais, Brazil
Keywords: Cichla ocellaris; Diplostomum; Mean intensity; Plagioscion squamosissimus; Pluviosity; Prevalence; Temperature; animal parasitosis; Brazil; cichla ocellaris; cichlid; diplostomum compactum; electric power plant; eye; female; fish; helminth; male; nonhuman; parasite identification; parasite prevalence; plagioscion squamosissimus; seasonal variation; water temperature; Animalia; Cichla; Cichlidae; Diplostomatidae; Diplostomum compactum; Plagioscion; Vermes